Współczesna rosyjska modlitwa poetycka. Modlitwa do Boga Ojca - Prus, Kazimierz (Rusycystyczne Studia Literaturoznawcze, 2014)
The article deals with Russian contemporary prayer poems where poets beg, thank and adore God. They write texts by paraphrasing ritual prayers and imitating them by anaclesis, anamnesis and addressative forms. Also, the poets make use of Orthodox formulas, and thus sacralize texts by introducing archaisms, syntactic parallelisms and repetitions of the whole stanzas and lines. The analyzed poetic prayers prove that a modern man makes requests to God in the main; seldom does he/she thank for God’s blessing or praise God.